Preparation and Characterization of LDPE and PP-Wood Fiber Composites - TAŞDEMİR, MÜNİR (WILEY, 2009)
Natural fiber reinforced composites is an emerging area in polymer science. These natural fibers are low cost fibers with low density and high specific properties. These are biodegradable and nonabrasive. The natural fiber composites offer specific properties comparable to those of conventional fiber composites. However, in development of these composites, the incompatibility of the fibers and poor resistance to moisture often reduce the potential of natural fibers, and these draw backs become critical issue. Wood-plastic composites (WPC) are a relatively new class of materials and one of the fastest growing sectors in the wood composites industry. Composites of wood in a thermoplastic matrix (wood-plastic composites) are considered a low maintenance solution to using wood in Outdoor applications. WPCs are normally made from a mixture of wood fiber, thermoplastic, and small amounts of process and property modifiers through an extrusion process. In this study, Wood-plastic composites (WPC) are produce by adding a maleic anhydride modified low density polyethylene coupling agent to improve interfacial adhesion between the wood fiber and the plastic. Mixing is done with twin screw extruder. Subsequently, tensile strength, the modulus of elasticity, % elongation, hardness, Izod impact strength, melt flow index (MFI), and heat deflection temperature (HDT) are determined. Thermal transition temperatures and microstructure are determined with DSC and SEM, respectively. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 30953102, 2009
Keywords: wood fiber; polyethylene; polypropylene; composite; mechanical properties; POLYETHYLENE; COMPATIBILIZER; POLYPROPYLENE; DISPERSION